Microsoft SQL Server AlwaysOn Solutions Guide for High Availability and Disaster Recovery - LeRoy, Tuttle (Microsoft, 2015)
You can make the best selection of a database technology for a high availability and disaster recovery solution when all stakeholders have a shared understanding of the related business drivers, challenges, and objectives of planning, managing, and measuring RTO and RPO objectives...